Insights into the evolution of a post-failure rock slope - R. Gerstner; C. Fey; E. Kuschel; F. Lehner; G. Valentin; K. Voit; C. Zangerl (Bulletin of Engineering Geology and the Environment, 2025)
Rock slope failure is commonly regarded as the most significant phase in the evolution of an unstable rock slope. However, many rock slopes do not fail in a single event but rather in several individual ones. Such polyphase rock slope failures impose a challenge, as their post-failure evolution is hard to predict, and the time interval between the failure events, their magnitude, and running-out distance can differ significantly for each respective event. In this study, we present a unique data-set of high-resolution remote sensing data acquired from a 170 m high, steep to overhanging post-failure rock slope over a 3.5-year survey. By applying ground-based interferometric synthetic aperture radar, unmanned aerial vehicle photogrammetry, and a 3D distance approach on terrestrial laser-scan data, we unravel the post-failure rock slope evolution on the example of the Hüttschlag study site (Salzburg, Austria). Accompanied by meteorological data and supported by a discrete element modelling approach, i.e. the asymmetric Voronoi logic, we (i) prove that the post-failure rock slope remains an active system, even 3.5 years after the latest major rock slope failure event, (ii) outline advantages and limitations of the respective remote sensing techniques, (iii) emphasise the challenge of identifying unambiguous triggers, and link this challenge to progressive failure within a fractured, anisotropic rock mass. Our findings highlight the importance of considering the time-dependency of rock mass strength and improve our understanding of post-failure rock slope evolution and rock mechanical processes in complex geological media.

100 Jahre Photogrammetrie-Innovation aus Heerbrugg - S. Heggli; K. Neumann; E. Voit (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2021)

Intragenic deletion in the LARGE gene causes Walker-Warburg syndrome - Jeroen van Reeuwijk; Prabhjit K. Grewal; Mustafa A. M. Salih; Daniel Beltrán-Valero de Bernabé; Jenny M. McLaughlan; Caroline B. Michielse; Ralf Herrmann; Jane E. Hewitt; Alice Steinbrecher; Mohamed Z. Seidahmed; Mohamed M. Shaheed; Abdullah Abomelha; et al. (Human Genetics, 2007)